2001
DOI: 10.1046/j.1462-2920.2001.00155.x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of copper on the microbial community of a coral reef sponge

Abstract: Marine sponges often harbour communities of symbiotic microorganisms that fulfil necessary functions for the well-being of their hosts. Microbial communities associated with the sponge Rhopaloeides odorabile were used as bioindicators for sublethal cupric ion (Cu2+) stress. A combined strategy incorporating molecular, cultivation and electron microscopy techniques was adopted to monitor changes in microbial diversity. The total density of sponge-associated bacteria and counts of the predominant cultivated symb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
61
0
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(65 citation statements)
references
References 44 publications
3
61
0
1
Order By: Relevance
“…The documented decline in coral reef ecosystems worldwide (Wilkinson, 2008) has prompted research into understanding how changing environmental conditions affect the close symbiotic associations of marine invertebrates (Webster et al, 2001;Bourne et al, 2008;Vega Thurber et al, 2008;Webster et al, 2008;Littman et al, 2010Littman et al, , 2011Webster et al, 2011). Only by studying marine invertebrates as holobionts (the host and all associated microbial communities) and better characterising the forces that structure their microbial associations will we be able to fully assess their capacity to adapt or acclimatise to environmental stress.…”
mentioning
confidence: 99%
“…The documented decline in coral reef ecosystems worldwide (Wilkinson, 2008) has prompted research into understanding how changing environmental conditions affect the close symbiotic associations of marine invertebrates (Webster et al, 2001;Bourne et al, 2008;Vega Thurber et al, 2008;Webster et al, 2008;Littman et al, 2010Littman et al, , 2011Webster et al, 2011). Only by studying marine invertebrates as holobionts (the host and all associated microbial communities) and better characterising the forces that structure their microbial associations will we be able to fully assess their capacity to adapt or acclimatise to environmental stress.…”
mentioning
confidence: 99%
“…They can provide additional nutrients and produce secondary metabolites that improve the defense of the host against predation, fouling and diseases (Hentschel et al, 2006;Taylor et al, 2007a). Several recent studies also correlate environmental parameters such as elevated seawater temperatures (Webster et al, 2008;Cebrian et al, 2011) or the presence of heavy metals (Webster et al, 2001;Selvin et al, 2009) with shifts in microbial communities and declines in sponge health.…”
Section: Introductionmentioning
confidence: 99%
“…Later on, the terms "low microbial abundance" (LMA) and "high microbial abundance" (HMA) sponges were coined to acknowledge the additional presence of archaea in sponge tissues (Hentschel et al, 2003). A typical HMA sponge contains 10 8 to 10 10 microorganisms/g sponge tissue, which can make up to 20%-35% of the sponge biomass (Reiswig, 1981;Webster et al, 2001;Hentschel et al, 2012); in contrast, only 10 5 to 10 6 bacteria/g sponge tissue are found in LMA sponges, which is roughly equivalent to the microbial abundances in seawater (Hentschel et al, 2006). This pattern extends to reproductive propagules in that the larvae of HMA sponges contain dense bacterial assemblages at the larval center, while the interior of LMA sponge larvae is largely free of microbes (Ereskovsky and Tokina, 2004;Maldonado, 2007;Schmitt et al, 2007;Gloeckner et al, 2013a, b).…”
Section: Introductionmentioning
confidence: 99%